Accuracy of mesiodistal teeth and dental arch width measurement with conventional plaster and digital model study - Zenia Adindaputri; Dyah Karunia; Darmawan Sutantyo (Journal of Dentomaxillofacial Science, 2021)
Objective: This study aims to determine the accuracy of the sum mesiodistal width and the arch width from the conventional plaster model, 2D digital scan, 3D intraoral scanning, and Cone Beam Computed Tomography (CBCT) methods. Material and Methods: The type of research in this study is a comparative experimental conducted by comparing 5 different sample groups. The study was conducted on 5 study models in each group, the control group (typodont), and the treatment group (the conventional plaster model, 2D digital scan, 3D intraoral scanning, and CBCT). The parameters measured were the sum of mesiodistal width and inter premolar. Each measurement was repeated 3 times by the same observer, then averaged. Statistical analysis using Pearson Correlation to determine the correlation between the accuracy of the measurement method compared to the control group (typodont). Results: The results showed that there was a significant accuracy correlation (p<0.05) in measuring the sum of mesiodistal width and inter premolar between the control group (typodont) using conventional plaster model measurement methods, 2D digital scan, 3D intraoral scanning, and CBCT. Conclusion: The conclusion of this study is conventional measurement methods, 2D digital scan, 3D intraoral scanning, and CBCT are accurate in measuring the sum of mesiodistal width and inter premolar width.